Determining the effect of apple and banana powders dried by sublimation on the quality indicators of a sour milk dessert during storage - Bandura (Kuzmyk), Uliana; Marynin, Andriy; Sviatnenko, Roman; Zheludenko, Julia; Kurmach, Mykhailo (My University, 2021)
The shelf life of sour milk dessert has been sub-stantiated based on the results of this study into the indicators of active acidity, water activity, enthalpy, and organoleptic properties. In addition, the content analysis of lactic acid bacteria and microbiological indicators in the finished product during storage was performed. It was found that the introduction of sublimated fruits together with whey protein concentrate reduces the water activ-ity index from 0.984 to 0.972 by increasing the con-centration of solids and product viscosity.The active acidity indicator acts in combina-tion with the water activity on the shelf life of food products. Active acidity during the study period was in the range of 5.4‒4.2 pH units. The biological and physiological value of the fermented milk product will increase due to the use of a starter culture containing microorganisms of bifidobacteria and lactobacilli, which include Streptococcus thermophilus, Lactobacillus del-brueckii ssp. Bulgaricus, Lactobacillus acidoph-ilus, Bifidobacterium lactis, Lactobacillus casei, Lactobacillus rhamnosus, Lactobacillus paraca-sei, Bifidobacterium infantis. When storing sour milk dessert for more than 3 days, the number of bacteria came down and was 1.0×108 CFU/g on day 9, which meets the regulatory requirements.Based on the results of microbiological indi-cators, the shelf life of the sour milk dessert was established, which should not exceed 5 days at a temperature of 4±2 °С.The development and improvement of sour milk desserts using secondary milk raw materi-als is a promising area of scientific research. This would allow the development of waste-free tech-nologies with the maximum use of useful compo-nents that are included in the secondary milk raw materials.
Keywords: dessert; freeze-dried powder; десерт кисломолочний; сублімований порошок; freeze-dried powder; проблемно-науково дослідна лабораторія